Perbedaan Status Anemia Gizi Besi Remaja Putri yang Bersekolah di SMA Program dan Non-Program Suplementasi Tablet Tambah Darah - Antun Rahmadi (Borneo Journal of Medical Laboratory Technology, 2018)
The results of Riskesdas in 2013 showed that the incidence of anemia in young women was still high at 22.7%. One of the efforts made by the Indonesian government in overcoming the problem of anemia in young women is by distributing iron supplementation tablets (TTD) to school girls. The TTD supplementation program for young women currently does not cover all educational institutions at the junior or senior high school level. This raises the question of whether there are differences in anemia status between schools that have implemented TTD supplementation programs and schools that have not implemented them. The general purpose of this study was to determine the anemia status of iron nutrition in high school students. The specific objectives of the study were to 1) assess the state of anemia in high school students with TTD supplementation program, 2) determine the status of anemia in high school students with non-TTD supplementation program and 3) find out the difference in the state of anemia between both high school students. The sample of this study was taken randomly from two schools in Bandar Lampung, namely SMK 1 as many as 75 people and Al-Azhar High School as many as 72 people. Data processing is carried out with the computer, and a different test is carried out by testing the kai quadratic statistics. The results showed that the incidence of anemia at SMK 1 was 24.0% while at Al-Azhar High School was 43.1%. There was a significant difference between the prevalence of anemia at SMK 1 Al-Azhar High School with a value of p = 0.023. The Health Service is expected to expand the coverage of the TTD program to schools that have not been covered by the TTD supplementation program. The school can participate in providing self-help TTD.